Diseño térmico y mecánico básico de una caldera de recuperación en el proceso de síntesis de amoníaco de la empresa Yara Colombia S.A.S. (2020)
The main objective of this project deals is to design a boiler for the recovery of waste heat from the synthesis gases of an ammonia plant. For this purpose, is to be realized the basic mechanical and thermal design of this boiler for its installation in the company YARA S.A.S Cartagena. The starting point of this project is the understanding of the design problem followed with the definition of specifications and wishes of the company. Afterwards, is carried out a market research and an investigation about which are the major manufacturers and their the offers for the product, as well as the study of the existing advances and limitations in the field to be studied. Then, the design and safety regulations and codes are established in order to create alternatives that comply with the technical requirements. Finally, is realized the selection of the most viable alternative for the project from a mechanical, thermal, economic and maintenance point of view. Likewise, is made the detailed design of the equipment, the definition of its working area and the protocols to be followed in its manufacture.